Activation of TRPV4 channel in pancreatic INS‐1E beta cells enhances glucose‐stimulated insulin secretion via calcium‐dependent mechanisms. Issue 19 (30th August 2013) - Skrzypski, M.; Kakkassery, M.; Mergler, S.; Grötzinger, C.; Khajavi, N.; Sassek, M.; Szczepankiewicz, D.; Wiedenmann, B.; Nowak, K.W.; Strowski, M.Z.
Abstract : Transient receptor potential channel vanilloid type 4 (TRPV4) is a Ca 2+ ‐ and Mg 2+ ‐permeable cation channel that influences oxidative metabolism and insulin sensitivity. The role of TRPV4 in pancreatic beta cells is largely unknown. Here, we characterize the role of TRPV4 in controlling intracellular Ca 2+ and insulin secretion in INS‐1E beta cells. Osmotic, thermal or pharmacological activation of TRPV4 caused a rapid rise of intracellular Ca 2+ and enhanced glucose‐stimulated insulin secretion. In the presence of the TRPV channel blocker ruthenium red (RuR) or after suppression of TRPV4 protein production, TRPV4 activators failed to increase [Ca 2+ ]i and insulin secretion in INS‐1E cells. Abstract : TRPV4 is expressed in pancreatic INS‐1E beta cells. Thermal, osmotic and pharmacological stimulation of TRPV4 increases [Ca 2+ ]i . TRPV4 activation leads to enhanced glucose‐induced insulin secretion.